Socioeconomic Status and Dropout of Children in Community Reading Center - Aidhil Putra; Irmawita Irmawita (Universitas Negeri Padang, 2021)
This research was motivated by the low encouragement of dropouts at the Community Reading Center of the Balai Gadang Village to continue their education, which was allegedly due to the low social condition of the family. The purpose of this study (1) is to describe how the social conditions of the family (2) describe the encouragement of children dropping out of school (3) to describe the relationship between family social conditions and the encouragement of children to drop out of school. The type of research used is quantitative correlation. There are 30 people as the population in this study. The technique for taking samples using random sampling, while the sample is 66% of the population to 20 people. The technique for collecting data is a questionnaire/questionnaire. The data analysis technique used theoretical ideal theory, percentage and Spearman Rho. The results of this study found that (1) the social conditions of the family were mostly quite low. (2) the encouragement of children dropping out of school is mostly quite low. (3) There is a significant relationship between family social conditions and the encouragement of children dropping out of school at the Community Reading Center of the Science Post, Balai Gadang Village. In connection with the existing conclusions, the researcher conveys that (1) It is hoped that parents will optimize in terms of looking for daily income and additional income so that their children can get a proper education. (2) It is expected that children who drop out of school can increase their motivation to learn. so that they can get a proper education and can learn both formally and non-formally. (3) It is hoped that more researchers can innovate by researching new variables in order to add and multiply existing variables.Keywords: family social conditions, encouragement of children dropping out of school